Optimizing Energy Efficiency in Acetone Production via Isopropyl Alcohol Dehydrogenation through Feed-Effluent Heat Integration - Regina Aditasya; Melisa Taslim; Sri Fatimah Azzahra; Bagas Bumi Narendro; Indira Avila Prantindoe; Kevin Setiadi Seng; Benaya Matius Marpaung (UPT Laboratorium Terpadu, Universitas Diponegoro, 2025)
Acetone production via isopropyl alcohol (IPA) dehydrogenation is an energy‑intensive process due to the endothermic nature of the reaction. This study aims to minimize net energy consumption by simulating a modified process design that incorporates a Feed‑Effluent Heat Exchanger (FEHE) strategy. The simulation results demonstrate that the modified configuration successfully recovers heat from the reactor effluent to preheat the feed stream to 178 °C, thereby reducing the total energy consumption from 4,695.8 kW to 4,532.0 kW. This energy saving of 163.8 kW confirms that the proposed heat integration is technically feasible and significantly enhances the thermodynamic efficiency of the acetone production process. Copyright © 2025 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).